2020
DOI: 10.3390/app10165524
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Evaluation of Solids Based on Deformation Wave Theory

Abstract: The application of a recent field theory of deformation and fracture to nondestructive testing (NDT) is discussed. Based on the principle known as the symmetry of physical laws, the present field theory formulates all stages of deformation including the fracturing stage on the same theoretical basis. The formalism derives wave equations that govern the spatiotemporal characteristics of the differential displacement field of solids under deformation. The evolution from the elastic to the plastic stage of deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…After that, reference [3] were experimentally verified. References [4][5] proposed and developed concepts such as phase dislocation, phase singularity, and vortex beam, and then conducted further research [6][7][8][9][10], gradually enriching the theory, generation, and related properties of vortex light. Reference [11] found that the vortex laser beam formed by Laguerre-Gauss (LG) beams had orbital angular momentum, and clearly determined the relationship between orbital angular momentum and vortex topological charge the relationship between.…”
Section: Introductionmentioning
confidence: 99%
“…After that, reference [3] were experimentally verified. References [4][5] proposed and developed concepts such as phase dislocation, phase singularity, and vortex beam, and then conducted further research [6][7][8][9][10], gradually enriching the theory, generation, and related properties of vortex light. Reference [11] found that the vortex laser beam formed by Laguerre-Gauss (LG) beams had orbital angular momentum, and clearly determined the relationship between orbital angular momentum and vortex topological charge the relationship between.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation behaviors of Al–Zn–Mg–Cu alloys were measured with the two-dimensional ESPI described in the previous work [ 9 ]. The experimental set-up is shown in Figure 1 .…”
Section: Espi Optical Measurement System and Analysis Algorithmmentioning
confidence: 99%
“…Yoshida et al [ 8 ] discusses the specific wave types that differentiate stages of deformation in association with the corresponding optical interferometric fringe patterns. In [ 9 ], Yoshida et al extend the discussion to the transition to the fracture and identify the shear band as manifestation of the solitary wave dynamics in association with micro-fracture and corresponding dislocation dynamics.…”
Section: Introductionmentioning
confidence: 99%